2017
DOI: 10.1021/acsami.7b13817
|View full text |Cite
|
Sign up to set email alerts
|

Superior Inorganic Ion Cofactors of Tetraborate Species Attaining Highly Efficient Heterogeneous Electrocatalysis for Water Oxidation on Cobalt Oxyhydroxide Nanoparticles

Abstract: A heterogeneous catalyst incorporating an inorganic ion cofactor for electrochemical water oxidation was exploited using a CoO(OH) nanoparticle layer-deposited electrode. The significant catalytic current for water oxidation was generated in a NaBO solution at pH 9.4 when applying 0.94 V versus Ag/AgCl in contrast to no catalytic current generation in the KSO solution at the same pH. HBO and BO ions were indicated to act as key cofactors for the induced catalytic activity of the CoO(OH) layer. The NaBO concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The other band (relatively weak) at 532.5 eV is attributed to the oxygen from the adsorbed hydroxyl contamination on the film surface. These XPS spectra in Co 2p and O 1s regions for the CoO(OH)‐NS film those were nearly the same as those for CoO(OH)‐NP film, (Figure S1a and b), ensuring that the chemical state of CoO(OH) is close between the CoO(OH)‐NS and CoO(OH)‐NP films.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The other band (relatively weak) at 532.5 eV is attributed to the oxygen from the adsorbed hydroxyl contamination on the film surface. These XPS spectra in Co 2p and O 1s regions for the CoO(OH)‐NS film those were nearly the same as those for CoO(OH)‐NP film, (Figure S1a and b), ensuring that the chemical state of CoO(OH) is close between the CoO(OH)‐NS and CoO(OH)‐NP films.…”
Section: Resultsmentioning
confidence: 99%
“…Electrocatalytic properties of the CoO(OH)‐NS electrode for water oxidation were investigated in a 0.1 M Na 2 B 4 O 7 solution at pH 9.4. Our recent study demonstrated that HB 4 O 7 − and B 4 O 7 2− ions in solution perform as excellent cofactors, acting as proton acceptors for accelerated O−O bond formation to induces efficient electrocatalytic water oxidation by the CoO(OH)‐NP film . Figure A shows the cyclic voltammograms (CVs) of the CoO(OH)‐NS electrodes with different Γ cov .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations